THE EFECT OF ACUPRESSURE ON DECREASING NAUSEA AND VOMITING IN THE FIRST TRIMESTER OF PREGNANCY IN THE WORK AREA OF THE SUKAHURIP HEALTH CENTER, GARUT REGENCY, WEST JAVA, 2020 - Nurulicha Nurulicha; Yulita Nengsih; Hartani Hartani (JURNAL KESEHATAN INDRA HUSADA, 2021)
Physical and psychological changes that afect complaints of nausea and vomiting or even hyperemesis, especially in the first trimester. Data at the Sukahurip Health Center, pregnant women who experience emesis in the first trimester is still high, namely in January-March 2020, which is as much as 70.7%. One of the non-pharmacological treatments for hyperemesis is acupressure massage. The purpose of this study was to determine the effect of acupressure on reducing nausea and vomiting (emesis) in the first trimester of pregnancy. The design of this research is quantitative research, pre-experimental approach using pre-test and post-test one-group design. The sample in this study were pregnant women in the first trimester who experienced nausea and vomiting. The data were obtained using an observation format, then analyzed by using the Paired Test. The results of this study showed that the frequency of nausea and vomiting before acupressure massage was 17.41 points, then after acupressure massage decreased to 10.47 points. The results of statistical tests using Paired test showed that there was an effect of acupressure on reducing complaints of nausea and vomiting in pregnant women with a p value of 0.000. The conclusion of this study is acupressure massage has an effect on reducing nausea and vomiting in first trimester pregnant women. Therefore, midwives can apply acupressure massage techniques to pregnant women to reduce nausea and vomiting as an effort to improve maternity services.